Edward Goodrich Acheson papers - Acheson, Edward Goodrich, 1856-1931.; Acheson, Edward Goodrich, 1856-1931.
Correspondence, diaries, laboratory notebooks relating to his various experiments and inventions, biographical material, financial records, newspaper clippings, and other papers relating to Acheson's career as an electrochemist, engineer, and inventor as well as to his companies. Includes a typescript of his autobiography entitled A Pathfinder: Discovery, Invention and Industry (1910), two volumes of court proceedings concerning a case in which Acheson's Carborundum Company was involved in 1894, and research materials of his biographer, Raymond Szymanowitz. Correspondents include John P. Deringer, Thomas A. Edison, Alfred E. Hunt, John Seys Huyler, Andrew W. Mellon, E.L. Nichols, Walther Rathenau, William Acheson Smith, and Edmund C. Sprague; Acheson's sons, Edward Acheson (1887-1962), George Wilson Acheson, John Huyler Acheson, and Raymond Mahler Acheson; and organizations including Bakewell & Bakewell, Cowles Electric Smelting and Aluminum Company, and the Electrochemical Society.
Electrochemist, engineer, and inventor.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Acheson, Edward Goodrich, -- 1887-1962 -- Correspondence; Acheson, George Wilson, -- 1892- -- Correspondence; Acheson, John Huyler, -- 1893-1938 -- Correspondence; Acheson, Raymond Mahler, -- 1888- -- Correspondence; Deringer, John P. -- Correspondence; Edison, Thomas A. -- 1847-1931 -- Correspondence; Hunt, Alfred E. -- 1855-1899 -- Correspondence; Huyler, John Seys, -- 1846-1910 -- Correspondence; Mellon, Andrew W. -- 1855-1937 -- Correspondence; Nichols, E. L. -- 1854-1937 -- Correspondence; Rathenau, Walther, -- 1867-1922 -- Correspondence; Smith, William Acheson -- Correspondence; Sprague, Edmund C. -- Correspondence; Szymanowitz, Raymond, -- 1898-; Bakewell & Bakewell -- Correspondence; Carborundum Company (Niagara Falls, N.Y.); Cowles Electric Smelting and Aluminum Company -- Correspondence; Electrochemical Society -- Correspondence; Chemistry; Electrochemistry; Inventions; Electrochemists; Engineers; Inventors